Gawky is a component of cytoplasmic mRNA processing bodies required for early Drosophila development. - Schneider, M.D.; Najand, N.; Chaker, S.; Pare, J.M.; Haskins, J.; Hughes, S.C.; Hobman, T.C.; Locke, J.; Simmonds, A.J. (Journal of Cell Biology, 2006)
In mammalian cells, the GW182 protein localizes to cytoplasmic bodies implicated in the regulation of messenger RNA (mRNA) stability, translation, and the RNA interference pathway. Many of these functions have also been assigned to analogous yeast cytoplasmic mRNA processing bodies. We have characterized the single Drosophila melanogaster homologue of the human GW182 protein family, which we have named Gawky (GW). Drosophila GW localizes to punctate, cytoplasmic foci in an RNA-dependent manner. Drosophila GW bodies (GWBs) appear to function analogously to human GWBs, as human GW182 colocalizes with GW when expressed in Drosophila cells. The RNA-induced silencing complex component Argonaute2 and orthologues of LSm4 and Xrn1 (Pacman) associated with 5'-3' mRNA degradation localize to some GWBs. Reducing GW activity by mutation or antibody injection during syncytial embryo development leads to abnormal nuclear divisions, demonstrating an early requirement for GWB-mediated cytoplasmic mRNA regulation. This suggests that gw represents a previously unknown member of a small group of genes that need to be expressed zygotically during early embryo development.